Model Rapid Application In Development Information Systems Population Data Processing (Case Study : Tambusai District Office In The Kabupaten Rokan Hulu Riau ) - Ramadhan, Muhammad Sabir; Aswati, Safrian; *, Iskandar (IJRDO -Journal of Computer Science Engineering, 2017)
Tambusai district office in the Kabupaten Rokan Hulu Riau Province is an instance that is currentlyresident in terms of data processing that is processed by computerization. But still using an applicationprogram such as Microsoft Word that affect some of the problems that is inaccurate population datainformation contained in these districts and population data duplication because absence of the key (key)to prevent duplication. In this case the data are processed population is active population data, populationdata and population data moved has died. It takes an information system to anticipate the issuesmentioned above. The information system is designed to implement the model of Rapid ApplicationDevelopment (RAD) where in generating the information system for processing data on population at theDistrict Office Tambusai the regency of Rokan Hulu, Riau Province through a number of phases,beginning with the planning phase requirement needs of the system, involving users to design and buildsystem (the activity is performed repeatedly to reach a mutual agreement), and the last stage ofimplementation.